REVENGE PORNOGRAPHY AS A FORM OF VIOLENCE AGAINST WOMEN - Dimovski, Darko T (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Violence is inherent in every society. Lately, with the use of modern technologies, another tool has been created, on the basis of which there is an even greater scope of victimization of women. This tool is reflected in the appearance of deepfake and revenge porn as new forms of violence against women. However, the subject of this paper’s analysis will only be revenge porn. Therefore, in the continuation of the work, after defining the concept of revenge pornography, the author gives an overview of normative solutions in certain countries. The next part of the paper is devoted to the characteristics of revenge pornography. Revenge pornography is the subject of analysis by the European Court of Human Rights in Strasbourg, the author analyzed the given case. After that, the normative framework in the Republic of Serbia was presented, viewed through the prism of revenge pornography. The last part of the responsibility falls on the fight against revenge pornography in order to provide as much protection as possible to women. Only in this way is it possible to increase women’s degree of security in state bodies that they will be provided with adequate protection against the misuse of modern technologies.